SOCIODEMOGRAPHIC AND REPRODUCTIVE FACTORS AFFECTING KNOWLEDGE OF MARRIED MEN ACCEPTING VASECTOMY - Zareen, Humaira; Shahzad, Saadia; Salahhudin, Mehmood (Journal of Ayub Medical College Abbottabad, 2016)
Background: Men's attitude is very important in the adoption of methods of contraception and limiting the family size. Men represent half the world's population, but account for less than one-third of contraceptive use. Knowledge of men about vasectomy as contraceptive method is also limited. The objectives of the study were to assess the knowledge of males about vasectomy in age group 25-50 years and to identify the factors affecting the knowledge of men regarding vasectomy. Methods: It was cross-sectional descriptive study. All the clients coming for vasectomy at Lahore General Hospital and Family Health Hospital were included in the study. Data was collected through questionnaire, which was entered in to computer using SPSS-17. Confidentiality of the data was ensured and verbal consent was obtained before data collection. Results: Majority (85.6%) of the men had adequate knowledge about vasectomy. Major source of knowledge, motivation and decision making regarding vasectomy were healthcare providers followed by friends and colleagues. Socio-demographic factors like age of the wife, education of men, income of men, media, friends and relatives showed association with knowledge about vasectomy. Conclusions: Almost all the respondents had formal education. Majority of the respondents had knowledge about vasectomy. Respondents acquired knowledge from health personnel, television, radio, newspapers, spouses and friends/colleagues. Misconception of the general population regarding vasectomy needs to be cleared and men should be involved actively in family planning programs. Health education program should be held at community level to educate people about the utilization of procedure. Keywords: Married male, vasectomy, factors, knowledge